Evaluation of anti-diarrheal activity of methanolic flesh extract of Flacourtia jangomas on mice - Susmita, Nusrat Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.